(untitled) (Journal of The Colloquium for Information Systems Security Education, 2025)
Quantum computing has a critical need to be integrated into the undergraduate classroom to meet the needs of cybersecurity education in the 21st Century and to prepare a robust quantum workforce. A cybersecurity laboratory that specializes in undergraduate research explored a pair of quantum security projects in order to develop the foundations of a rich pedagogy to realize these needs: one on cracking pseudo-RSA, and one on understanding the limitations of quantum machine learning in aiding LLM development and refinement. This paper explores why this integration is necessary, explicates the research projects undertaken by these undergraduate researchers, and discusses their contributions to applied quantum security. Our contribution is to provide a template for how to quickly and effectively establish a multidisciplinary quantum security pedagogy for undergraduate students, provide example projects that can be adapted to student interests and abilities, and demonstrate how to enroll students from a wide variety of disciplines, increasing diversity and resiliency in quantum cybersecurity and cybersecurity broadly.